Coextraction of Thrombomodulin and Tissue Factor from Human Placenta: Effects of Concanavalin A and Phospholipid Environment on Activity - Freyssinet, Jean-Marie; Brami, Brigitte; Gauchy, Josiane; Cazenave, Jean-Pierre (Thrombosis and Haemostasis, 1986)
Thrombomodulin and tissue factor activities have been coextracted from human placenta by several non-ionic detergents, n-octylglucoside and Triton X-100 being the most efficient ones. The n-octylglucoside placenta extract had a strong cofactor activity in the activation of human protein C by human a-thrombin. Treatment of the n-octylglucoside and Triton X-100 placenta extracts by phospholipases C and A2 revealed that an adequate phospholipid environment is necessary for maximal thrombomodulin activity, while it is well known that this is crucial for tissue factor activity. Soluble concanavalin A reversibly inhibited thrombomodulin and tissue factor activities to the same extent. Con-A-Sepharose affinity chromatography of the Triton X-100 placenta extract resulted in the same proportion (30%) of these two activities bound to the lectin, which were subsequently eluted in the same fractions by a linear gradient of α-methyl-D-glucoside. This observation suggests that thrombomodulin activity is associated to a glycoprotein component presenting the same degree of carbohydrate heterogeneity, involving α-D-mannosyl or α-D-glucosyl residues, as tissue factor apoprotein. Relipidation of fraction eluted by α-methyl-D-glucoside was essential to detect tissue factor activity, it was also necessary to recover full thrombomodulin activity. An antibody to human brain tissue factor apoprotein inhibited human placenta tissue factor activity, whereas thrombomodulin activity was unaffected, suggesting that these two cellular activities are related to distinct molecular entities sharing striking functional and structural similarities.
Keywords: Thrombomodulin; Tissue factor; Phospholipid; Glycosyla-tion heterogeneity; Protein C